Rationalized inhibition of mixed lineage kinase 3 and CD70 enhances life span and antitumor efficacy of CD8+ T cells. Issue 2 (5th August 2020) - Kumar, Sandeep; Singh, Sunil Kumar; Viswakarma, Navin; Sondarva, Gautam; Nair, Rakesh Sathish; Sethupathi, Periannan; Dorman, Matthew; Sinha, Subhash C; Hoskins, Kent; Thatcher, Gregory; Rana, Basabi; Rana, Ajay
Abstract : Background: The mitogen-activated protein kinases (MAPKs) are important for T cell survival and their effector function. Mixed lineage kinase 3 (MLK3) (MAP3K11) is an upstream regulator of MAP kinases and emerging as a potential candidate for targeted cancer therapy; yet, its role in T cell survival and effector function is not known. Methods: T cell phenotypes, apoptosis and intracellular cytokine expressions were analyzed by flow cytometry. The apoptosis-associated gene expressions in CD8 + CD38 + T cells were measured using RT 2 PCR array. In vivo effect of combined blockade of MLK3 and CD70 was analyzed in 4T1 tumor model in immunocompetent mice. The serum level of tumor necrosis factor-α (TNFα) was quantified by enzyme-linked immunosorbent assay. Results: We report that genetic loss or pharmacological inhibition of MLK3 induces CD70-TNFα-TNFRSF1a axis-mediated apoptosis in CD8 + T cells. The genetic loss of MLK3 decreases CD8 + T cell population, whereas CD4 + T cells are partially increased under basal condition. Moreover, the loss of MLK3 induces CD70-mediated apoptosis in CD8 + T cells but not in CD4 + T cells. Among the activated CD8 + T cell phenotypes, CD8 + CD38 + T cell population shows more than five fold increase in apoptosis due to loss of MLK3, and the expression of TNFRSF1a is significantly higher in CD8 + CD38 + T cells. In addition, we observed that CD70 is an upstream regulator of TNFα-TNFRSF1a axis and necessary for induction of apoptosis in CD8 + T cells. Importantly, blockade of CD70 attenuates apoptosis and enhances effector function of CD8 + T cells from MLK3 −/− mice. In immune-competent breast cancer mouse model, pharmacological inhibition of MLK3 along with CD70 increased tumor infiltration of cytotoxic CD8 + T cells, leading to reduction in tumor burden largely via mitochondrial apoptosis. Conclusion: Together, these results demonstrate that MLK3 plays an important role in CD8 + T cell survival and effector function and MLK3-CD70 axis could serve as a potential target in cancer.